Associations of dietary macronutrients and micronutrients with the traditional and nontraditional risk factors for cardiovascular disease among hemodialysis patients: A clinical cross-sectional study. Issue 26 (June 2018) - Duong, Tuyen Van; Wong, Te-Chih; Su, Chien-Tien; Chen, Hsi-Hsien; Chen, Tzen-Wen; Chen, Tso-Hsiao; Hsu, Yung-Ho; Peng, Sheng-Jeng; Kuo, Ko-Lin; Liu, Hsiang-Chung; Lin, En-Tsu; Yang, Shwu-Huey
Abstract : Abstract: The current study was to examine the association of adequate intake of macronutrients and micronutrients with traditional and nontraditional cardiovascular risk factors in hemodialysis patients. A clinical cross-sectional study was conducted between September 2013 and April 2017 on 492 hemodialysis patients aged 20 years and above, received thrice-weekly hemodialysis treatment for at least 3 months, adequate dialysis quality (equilibrated Kt/V ≥ 1.2 g/kg/d) from 7 hospital-based hemodialysis centers in Taiwan. The dietary intake was evaluated by the 3-day dietary record, and a 24-hour dietary recall. Biochemical parameters were archived from laboratory tests. The cardiovascular disease (CVD) risk factors were defined by the Kidney Disease Outcomes Quality Initiative (K/DOQI) Clinical Practice Guidelines. The adequate dietary intake of macronutrients and micronutrients was recommended by the European Best Practice Guidelines, K/DOQI, and Institute of Medicine guidelines. Logistic regression analysis was used. All hemodialysis patients had CVD risks, the lowest proportion of patients with adequate intake of macronutrients and micronutrients were 8.7% and 1.8%, respectively. The adequate dietary intake associated with lower likelihood of having CVD risks in hemodialysis patient by 47% to 84%, including 39% to 58% lower hypertension, 37% to 50% lower dyslipidemia, 42% to 63% diabetes mellitus, 44% to 84% lower obesity, 58% lower low calcium, 38% lower hyperparathyroidism, 47% to 64% lower hyperhomocysteinemia, and 41% to 67% lower inflammation, 63% to 74% lower hypoalbumin, 73% lower inadequate normalized protein nitrogen appearance. Adequate dietary nutrients intake may reduce the cardiovascular risks factors, in turn, to prevent the cardiovascular morbidity and mortality.